A survey on security and policy aspects of blockchain technology - Haider Hadi Abbas; Montadher Issam Abdul Kareem; Hassan Muwafaq Gheni (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
This survey talks about the problem of security and privacy in the blockchain ecosystem which is currently a hot issue in the blockchain community. The survey intended to study this problem by considering different types of attacks in the blockchain network with respect to algorithms presented. After a preliminary literature review it seems that some focus has been given to study the first use case while, to the best of my knowledge, the second use case requires more attention when blockchain is applied to study it. The research is also interested in exploring the link between these two use cases to study the overall data ownership preserving accountable system which will be a novel contribution of this work. However, due to the subsequent government mandated secrecy around the implementation of data encryption standard (DES), and the distrust of the academic community because of this, a movement was spawned that put a premium on individual privacy and decentralized control. This movement brought together the top minds in encryption and spawned the technology we know of as blockchain today. This survey explores the genesis of encryption, its early adoption, and the government meddling which eventually spawned a movement which gave birth to the ideas behind blockchain.